Modern dynamical systems and applications dedicated to Anatole Katok on his 60th birthday - Brin Michael; Hasselblatt Boris; Pesin Yakov (Cambridge CUP, 2004)
This volume covered major areas include hyperbolic dynamics, elliptic dynamics, mechanics, geometry, ergodic theory, group actions, rigidity, applications.
Keywords: Dynamical systems